2014
DOI: 10.3221/igf-esis.30.28
|View full text |Cite
|
Sign up to set email alerts
|

On the use of the Theory of Critical Distances to estimate the dynamic strength of notched 6063-T5 aluminium alloy

Abstract: In this paper the so-called Theory of Critical Distances is reformulated to make it suitable for estimating the strength of notched metals subjected to dynamic loading. The TCD takes as its starting point the assumption that engineering materials' strength can accurately be predicted by directly post-processing the entire linear-elastic stress field acting on the material in the vicinity of the stress concentrator being assessed. In order to extend the used of the TCD to situations involving dynamic loading, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To quantify the critical radius, where a significant change in the state of field stress along propagating fracture occurs, the theory of critical distance (TCD) (Taylor, 2007) was applied and further extended in this study. The critical distances (TCD) found application in predicting fatigue and failure in a wide range of materials and components (Taylor, 2007;Yin et al, 2014;Louks et al, 2014). The TCD was also applied towards predicting fracture of rocks and minerals (Lajtai, 1971;Ito et al, 1991).…”
Section: Critical Radiusmentioning
confidence: 99%
“…To quantify the critical radius, where a significant change in the state of field stress along propagating fracture occurs, the theory of critical distance (TCD) (Taylor, 2007) was applied and further extended in this study. The critical distances (TCD) found application in predicting fatigue and failure in a wide range of materials and components (Taylor, 2007;Yin et al, 2014;Louks et al, 2014). The TCD was also applied towards predicting fracture of rocks and minerals (Lajtai, 1971;Ito et al, 1991).…”
Section: Critical Radiusmentioning
confidence: 99%
“…It has also been proved that the TCD can be used to predict static fracture in ductile metallic materials containing various stress raisers and subjected to both uniaxial and multiaxial loading [8]. Moreover, in papers [9,10] was shown that Theory of Critical Distances is suitable for predicting the strength of notched metallic materials subjected to dynamic loading.…”
Section: Introductionmentioning
confidence: 99%
“…This fact requires the creation of adequate models and methods to predict the mechanical behavior of the materials in a wide range of the conditions of external effects, including intensive dynamic loads for materials having both direct and inverse strain rate sensitivity in view of the effect of the non-local destruction in the area of stress concentrators. To overcome this problem, we propose to use a theory of critical distance (TCD), whose effectiveness has already been shown for the prediction of the fracture of laboratory specimens of various materials and a complex geometry under quasistatic and dynamic loading [2,3]. …”
Section: Introductionmentioning
confidence: 99%